Implementation of Pancasila Learner Profile-Based Attitude Assessment for Junior High School Civics Study Field Based on Phase D in the Merdeka Curriculum Era - Brata, Diah Puji Nali (EDUTEC : Journal of Education And Technology, 2024)
Indonesia's education system is facing numerous challenges due to the rapid development of information and communication technology, resulting in students being perceived as less empathetic and less skilled in addressing social issues. The Pancasila Student Profile is a policy by the Ministry of Education and Culture within the Merdeka Curriculum to strengthen national character. This study aims to analyze the implementation of the Merdeka Curriculum in Civics subjects, the attitude assessment models, and the supporting and inhibiting factors. The research employs a qualitative approach, with the subjects including the principal, curriculum vice-secretary, Civics teachers, and students. Data collection is conducted through source and technique triangulation, while data analysis involves data reduction, data display, and data verification. The findings reveal that the implementation of the Civics Curriculum has altered the concepts and meanings outlined in the teaching module; learning and assessment are now an integrated unit; the material's scope is more comprehensive according to the learning outcomes of four key elements (Pancasila, the 1945 Constitution, Unity in Diversity, and the Unitary State of the Republic of Indonesia) in phase D. The assessment model in the Merdeka Curriculum encompasses cognitive (formative, summative) and psychomotor (projects, practice, products) assessments as a unified whole. Attitude assessment is based on the Pancasila Student Profile (P5) strengthening program, with the selection of dimensions tailored to the objectives, subject matter, and the P5 theme set by the school. Daily assessments are the basis for the Pancasila Learner Profile-based attitude report card. Supporting factors include the synergy of the school community in implementing P5, while obstacles include some teachers' lack of understanding of the indicators in the six elements and sub-elements of the Pancasila Learner Profile, with assessments still being manual and done in Excel.